2021
DOI: 10.1111/cas.14810
|View full text |Cite
|
Sign up to set email alerts
|

ZHX3 promotes the progression of urothelial carcinoma of the bladder via repressing of RGS2 and is a novel substrate of TRIM21

Abstract: Clinically, patients with urothelial carcinoma of the bladder (UCB) with tumor metastasis are incurable. To find new therapeutic strategies, the mechanisms underlying UCB invasion and metastasis should be further investigated. In this study, zinc finger and homeobox 3 (ZHX3) was first screened as a critical oncogenic factor associated with poor prognosis in a UCB dataset from The Cancer Genome Atlas (TCGA). These results were also confirmed in a large cohort of clinical UCB clinical samples. Next, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 37 publications
(54 reference statements)
3
20
0
Order By: Relevance
“…Two signature genes (ZHX3 and SUZ12) were positively correlated with the occurrence of BC, while a negative correlation was instead determined for the remaining 5 genes (ZNF350, ZNRD1, ZNF195, APEX2, and EBF4). In line with a recent study [ 18 ], our results showed that ZHX3 plays an oncogenic role in BC pathogenesis. Interestingly, ZHX3 has also shown to act as a tumor suppressor in renal cell carcinoma [ 19 ], breast cancer [ 20 ], and liver cancer [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Two signature genes (ZHX3 and SUZ12) were positively correlated with the occurrence of BC, while a negative correlation was instead determined for the remaining 5 genes (ZNF350, ZNRD1, ZNF195, APEX2, and EBF4). In line with a recent study [ 18 ], our results showed that ZHX3 plays an oncogenic role in BC pathogenesis. Interestingly, ZHX3 has also shown to act as a tumor suppressor in renal cell carcinoma [ 19 ], breast cancer [ 20 ], and liver cancer [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Together, this suggests that both AR-mediated effects in cell migration and colony formation in UM-UC-3-AR are tightly linked. With these phenotypic changes, several genes were significantly upregulated upon hormone stimulation, among which some previously described for their role in promoting migration and colony formation of diverse type of cancer models such as FKBP5, LDH-A, GREB1, PDLIM1, TNK2, VASP, ARHGAP31 and ZHX3 [40][41][42][43][44][45][46][47], and genes known to drive the development of cancer cells with stem cell-like characteristics such as TFCP2L1 and SH3RF3 [48,49]. These genes were consistently downregulated upon treatment with enzalutamide or after AR knockdown, which validates them as androgen-responsive genes.…”
Section: Discussionmentioning
confidence: 92%
“…Our study is the first research that identified the risk of RGS19 on BLCA by means of bioinformatic analysis in combination with experiment. In addition, we found a potential therapeutic drug, GSK1070916, for BLCA patients with high expression of RGS19 [31][32][33][34].…”
Section: Discussionmentioning
confidence: 93%